When does the discount look more attractive: neural correlates of discount framing effect in the purchase of bundles. Issue 10 (3rd July 2019) - Mo, Zan; Ma, Haiying; Wei, Wei; Wang, Cuicui; Fu, Huijian
Abstract : Bundling, as a common selling strategy, is often used along with a price discount. However, relatively little is known about the neural correlates of discount framing effect in the bundling context. In the current study, we recorded event-related potentials while participants were performing a virtual shopping task in which they had to decide whether or not to buy bundles. Each bundle consisted of a relatively high-priced product and a relatively low-priced product, and three discount frames with practically identical total prices were devised for each bundle. The price reduction was described either as a discount on the individual component [discount on the high-priced product (DH); discount on the low-priced product (DL)] or on the overall bundle (DB). Behavioral data showed that DH and DB led to higher purchase rate than DL. Electrophysiological data revealed increased P300 amplitudes for DH and DB relative to DL, which was suggestive of the cognitive process of evaluative categorization. In addition, attenuated LPP amplitudes were observed for DH and DL compared with DB, indicating higher cognitive load for DH and DL. Overall, these results demonstrate the discount framing effect in the purchase of bundles and the potential neural correlates of this effect.